DESKRIPSI KETERAMPILAN PROSES SAINS SISWA KELAS XI IPA SMA NEGERI 2 SUNGAI RAYA PADA MATERI ASAM BASA - Nurliani, Nurliani; Sartika, Rody Putra; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to describe science process skills and cause of the low of student science process skill on acid-base material. The form of this study was descriptive with study case method. The subjects were 30 students of class XI IPA 1 SMA Negeri 2 Sungai Raya. According to data analysis, students were  very skilled in  observing and grouping aspects which score were 100% and 90% respectively. Students was skilled at making predictions aspects there which score was 64.16%. Students was less skilled in data analysis and concluding aspects which score were 48.33% and 35.83% respectively. Cause of the low of student science process skill was students have difficulties as follows (a) they didn’t know to write prediction, didn’t know to investigate, and less confidence with their opinion; (b) didn’t read the question correctly; (c) unaccustomed to participate in working group reports in groups activities and can’t explain based on the grid; And (d) unaccustomed to make conclusion. Keywords: Science Process Skills, Acid Base Material